Doing qualitative research designs, methods, and techniques - Garner, Roberta (Pearson Education, 2013)
This text is ideal for classes in disciplines such as cultural studies, anthropology, political science, ethnic studies, women and gender studies, the media, journalism and communications, organizational behavior, and more.